Festival Paras Beswara Sebagai Rintisan Desa Wisata Budaya - Ranangsari, Widi Lindi; Putra, Trisna Pradita; Ranangsari, Kosalalita Anggiyumna (JURNAL DESTINASI PARIWISATA; Vol 12 No 1 (2024): VOL 12, NO 1 (2024): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2024)
Mojokerto as a region where the former Majapahit kingdom passed on the spirit to the local younger generation in terms of cultural development, local wisdom, and environmental sustainability through the holding of the Paras Beswara Festival in hamlet Paras, subdistrict Pacet. The research used a qualitative descriptive research in researching the implementation of the Paras Beswara Festival. Data collection was carried out through field observations at the time of the festival accompanied by interviews with the organizers, as well as completed by literature studies and analyzed with interactive model analysis including reduction, presentation, drawing conclusions and verification. The results of the study show that festivals in the form of cultural workshops, bamboo murals, fun outbound, keroncong in the middle of the rice fields, ngopi coro mbahku, ngunduh patirtan, cultural carnivals, and earth alms (sedekah bumi) are held in mutual cooperation (gotong royong) and joyful by rural residents. The organizing of the festival emphasizes the tradition of gotongroyong as a form of collective action, trust from residents, motivation to move forward together, open and friendly communication within the family atmosphere and is loaded with educational value for the younger generation. Keywords: festivals; Mojokerto; rural; culture; management